The expression of p53, ki67 and COX-2 in erosive-type oral lichen planus: Expression of p53, ki67, and COX-2 in Oral lichen planus - Aziz, Sayf; Hamad, Shehab; Qasim, Yosra (Cellular and Molecular Biology, 2023)
Oral lichen planus is a chronic inflammatory disease that affects the oral mucosa and may undergo malignant changes, which can be reflected in the expression of specific proteins that are responsible for maintaining cellular mitosis and apoptosis. The study aimed to investigate the expression of p53, ki67, and COX-2 in erosive lichen planus using immunohistochemistry to correlate these findings with the histological aspects of the disease. Thirty-three biopsies of erosive lichen planus were collected and diagnosed based on histological and clinical criteria. The blocks were processed for immunohistochemistry to assess p53, ki67, and COX-2 expression in the basal layer, suprabasal, and inflammatory infiltrate respectively. The histological analysis of the samples showed no dysplasia or metastasis. P53 stained positively in 80% of the samples, while ki67 was positive in all the cases, ranging from 5% to 85% positivity. COX-2 expression ranged from 0-50% positivity. The highest expression of p53 was observed in 8 cases (24.2%), with a maximum of 5%, and ki67 exhibited the highest expression of 90% in 3 cases (9.1%). COX-2 was negative in 27 cases (81.8%) and positive in 6 cases (18.1%), with the highest expression at 50% in 1 case and 10 % positivity in 4 cases (12.1%). In our study, the markers p53, ki67, and COX-2 proved to be useful for detecting the proliferative, inflammatory, and physiologic states of the keratinocytes. However, they did not demonstrate utility in detecting any malignant transformation.